The The trend develops administration quality studies of Pondok Modern Darussalam Gontor: Armadruchdee Heemphinit Ahamakosee Kasor Weyusoh Sidek - Heemphinit, Armadruchdee; Kasor, Ahamakosee; Sidek, Weyusoh (Al-HIKMAH Journal, 2024)
This article has the objective for presents the knowledge about the trend develops administration quality studies of Pondok Modern Darussalam Gontor , be the article researches a document , pick collect document data , the book and straight experience , and bring analyses the substance (Content analysis) , from the education meets that , the trend that cause Pondok Modern Darussalam Gontor is of good quality in the administration studies , be administration systematization studies that lead with 5 points spirits in order important in the driving moves every work institute practice , the spirit aforementioned is (Panca jiwa) , be , the mind is pure , (Jiwa Keikhlassan) , enough mind is (Jiwa Kesederhanaan) , the mind makes a stand with oneself (Jiwa Kemandirian) , the be relatives Islam mind , (Jiwa Ukhuwah Islamiyyah) , and free mind , (Jiwa Kebebasan) , for , the student has and everybody personnel have been performing one’s duty and live in this world happily and affect to build [ wasp ] the return that are valuable in day the next life with.